2013
DOI: 10.5702/massspectrometry.a0019
|View full text |Cite
|
Sign up to set email alerts
|

5-Nitrosalicylic Acid as a Novel Matrix for In-Source Decay in Matrix-Assisted Laser Desorption/Ionization Mass Spectrometry

Abstract: The matrix-assisted laser desorption/ionization in-source decay (MALDI-ISD) of peptides and glycans was studied using an oxidizing chemical, 5-nitrosalicylic acid (5-NSA) as the matrix. The use of 5-NSA for the MALDI-ISD of peptides and glycans promoted fragmentation pathways involving "hydrogen-deficient" radical precursors. Hydrogen abstraction from peptides resulted in the production of a "hydrogen-deficient" peptide radical that contained a radical site on the amide nitrogen in the peptide backbone with su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
8
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 55 publications
2
8
0
Order By: Relevance
“…In contrast, 5‐NSA could function as donor of oxygen atoms; thus, IM5b produced [M − H + O], which is denoted as [M + 15] γ • in Figure 5. The counterpart is [5‐NSA − O], which was observed as a protonated form in the MALDI mass spectrum of 5‐NSA 19 . The transition state for the formation of [M + 15] γ • and [5‐NSA − O] was TS5b, and the corresponding barrier was 82 kJ mol −1 .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In contrast, 5‐NSA could function as donor of oxygen atoms; thus, IM5b produced [M − H + O], which is denoted as [M + 15] γ • in Figure 5. The counterpart is [5‐NSA − O], which was observed as a protonated form in the MALDI mass spectrum of 5‐NSA 19 . The transition state for the formation of [M + 15] γ • and [5‐NSA − O] was TS5b, and the corresponding barrier was 82 kJ mol −1 .…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, MALDI‐ISD using an oxidizing matrix is concluded to produce [a]•/[x − H] fragment pair through a nitrogen‐centered radical intermediate (Scheme 1A). 2,18,19 …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Among other matrices to have been investigated for carbohydrate analysis, 5‐nitrosalicylic acid ( 13 ), which has oxidizing properties has been used to ionize both peptides and carbohydrates (Asakawa, ). A feature of the spectra of carbohydrates (positive ion) were fragment ions produced by hydrogen abstraction from hydroxyl groups to give a hydrogen‐deficient glycan radical which fragmented to yield high‐abundance cross‐ring cleavage products in a similar manner to the production of highly‐informative fragmentation spectra of N ‐linked glycans observed in negative ion mode (Harvey et al, ).…”
Section: Matricesmentioning
confidence: 99%
“…MALDI-ISD protein fragmentation occurs both in positively and negatively charged species. The fragmentation mechanism of MALDI-ISD using reducing matrices involves the transfer of a hydrogen atom from the matrix molecule to the carbonyl group on the backbone of a protein. ,, This event leads to the formation of radical ions, which can fragment to generate c′ and radical z ions. These latter ion species can form z, z′, and matrix-adducted z ions. , The intensity of MALDI-ISD fragment ions detected in either negative or positive ion mode is influenced by the presence of acidic or basic amino acid residues, respectively. , The negative ionization mode is beneficial for the MALDI-ISD MS analysis of acidic peptides. , The larger fragment ions more likely include both acidic and basic residues and consequently show similar relative intensities in positive and negative ion mode MALDI-ISD MS, although the latter, in general, provides lower sensitivity. ,, Since the amino acid sequence regions close to the protein termini may be biased toward basic or acidic residues, MALDI-ISD fragmentation in this region can result in different efficiencies of ionization, depending on the mode used. For example, Asakawa analyzed myoglobin by both positive and negative ion MALDI-ISD TOF MS and showed that fragment ions smaller than m / z 1000 were detected in the negative ion mode to provide sequence information complementary to the positive ion mode analysis, resulting in an improved sequence coverage of 67% …”
Section: Introductionmentioning
confidence: 99%